More Alike, More Forgiving: What Builds Stronger Student Friendships? - Faruq, Dara Asmarani; Agung M. Iqbal; Annisa Fitriani (ANFUSINA: Journal of Psychology, 2023)
This study examines the relationship between forgiveness, similarity, and friendship quality among students at the Faculty of Da'wah and Communication Sciences, UIN Raden Intan Lampung. A correlational quantitative method was employed with 65 participants selected via purposive sampling. Three psychological scales were used: Friendship Quality Scale (α=0.836), Forgiveness Scale (α=0.880), and Similarity Scale (α=0.927). Multiple regression analysis revealed significant relationships between variables (R=0.498; p<0.001) with a combined contribution of 24.8%. Partial analysis showed moderate correlation between forgiveness and friendship quality (r=0.321; p=0.009), while similarity demonstrated stronger correlation (r=0.417; p<0.001). Notably, similarity contributed more substantially (16%) than forgiveness (8.7%) to friendship quality, indicating that group homogeneity factors outweigh forgiveness capacity in maintaining peer relationships among university students. Keywords : emerging adulthood, friendship quality, interpersonal relationships, forgiveness